A pediatric case of disseminated mutilating lupus vulgaris: A disgrace for society - Suresh Kumar Jain; Prafull Mehta; Savera Gupta; Ramesh Kumar (Wolters Kluwer Medknow Publications, 2016)
Lupus vulgaris (LV) is a chronic and progressive form of cutaneous tuberculosis. The lesions may sometimes be associated with extensive destruction of tissue resulting in marked disfigurement and morbidity. A high index of suspicion is crucial for early diagnosis and treatment and thereby prevention of cosmetic deformity. Lupus vulgaris presenting as disseminated mutilating lesions in a child is uncommon, especially in today's era. Herein, we report an unusual case of lupus vulgaris with coexistence of multiple ulcerative mutilating lesions over face and classical plaque over distant site (right thigh) in a 9 year old girl.